Assessment of InSight Landing Site Predictions. Issue 8 (7th August 2020) - Golombek, M.; Kass, D.; Williams, N.; Warner, N.; Daubar, I.; Piqueux, S.; Charalambous, C.; Pike, W. T.
Abstract: Comprehensive analysis of remote sensing data used to select the Interior Exploration using Seismic Investigations, Geodesy and Heat Transport (InSight) landing site correctly predicted the atmospheric temperature and pressure profile during entry and descent, the safe landing surface, and the geologic setting of the site. The smooth plains upon which the InSight landing site is located were accurately predicted to be generally similar to the Mars Exploration Rover Spirit landing site with relatively low rock abundance, low slopes, and a moderately dusty surface with a 3–10 m impact fragmented regolith over Hesperian to Early Amazonian basaltic lava flows. The deceleration profile and surface pressure encountered by the spacecraft during entry, descent, and landing compared well (within 1 σ ) of the envelope of modeled temperature profiles and the expected surface pressure. Orbital estimates of thermal inertia are similar to surface radiometer measurements, and materials at the surface are dominated by poorly consolidated sand as expected. Thin coatings of bright atmospheric dust on the surface were as indicated by orbital albedo and dust cover index measurements. Orbital estimates of rock abundance from shadow measurements in high‐resolution images and thermal differencing indicated very low rock abundance and surface counts show 1–4% area covered by rocks. Slopes at 100 to 5 m length scale measured from orbital topographic and radar data correctly indicated a surface comparably smooth and flat as the two smoothest landing sites (Opportunity and Phoenix). Thermal inertia and radar data indicated the surface would be load bearing as found. Plain Language Summary: Orbital remote sensing data were used to select the landing site for InSight and to confirm that the surface met the engineering constraints required for a safe landing and successful instrument deployment. By relating remote sensing signatures to surface characteristics at landing sites, these sites can be used as ground truth for orbital data and are essential for selecting and validating landing sites for future missions. Models of the atmosphere that included monitoring during approach by orbiting spacecraft compared well with the deceleration profile and surface pressure encountered by the spacecraft during entry, descent, and landing, and the spacecraft landed successfully. The smooth plains on which InSight landed are consistent with expectations made prior to landing. Remote sensing data indicated that the InSight landing site would be similar to the Mars Exploration Rover Spirit landing site. Both sites have relatively low rock abundance, low slopes, and a moderately dusty surface, with a 3–10 m impact fragmented regolith over Hesperian to Early Amazonian basaltic lava flows. Key Points: The atmosphere, safe surface, and geologic setting of the landing site were correctly predicted by remote sensing data before landing The modeled atmospheric temperature profiles and surface pressure were within 1 sigma of the measured deceleration profile and surface pressure InSight's surface is similar to Spirit's with low rock abundance, low slopes, moderate dust, and is composed of impact regolith over basalt